Perubahan Pola Pendengar Radio Segmentasi Dewasa Muda Di Kota Bandung - Taufiq Furqon Nurhakim; Muhammad Fazri Candra (Program Studi Hubungan Masyarakat Politeknik LP3I, 2022)
This research examines the context of digital communication and explores audience assessment and survey strategies for radio, to analyze the influence of technology on new research methodologies and re-conceptualize the audience, especially the concept of listeners. This study uses a qualitative approach using Stuard Hall theory, presents new insights into the method of audience assessment and the concept of radio listeners.The results of this study have relevant conclusions and are found about the influence of digitalization and audience behavior. Consider the audience's main concepts and listeners which shows that the audience's main concepts and listeners, conventional radio broadcast broadcasting and audience research are observed to be out-dated or, at least inappropriate to describe today's cross-media, multiplatform and multitasking behavior about media, especially radio.